Catálogo dos impressos musicais do acervo Balthasar de Freitas: subsídios para o estudo das atividades musicais em Goiás da segunda metade do século XIX à primeira metade do século XX - Silva, Rodrigo Alves da (2019)
The present dissertation aims to present a description of printed music in Balthasar de Freitas’s collection. This description includes the preparation of a catalog of such documents as well as the analysis of the information collected in the cataloging. Based on the analysis of Brazilian Standard of Archival Description – NOBRADE, international standards for the cataloging of musical printed materials, and the analysis of catalogs of printed music published in Brazil, a set of descriptive elements was established that includes identification code, title, genre, composer, publisher, date of publication, among others. In a second moment, the information collected in the cataloging was analyzed within the context of the musical activities in Goiás from later 19th century to earlier 20th century. The results show that printed music in Balthasar de Freitas’s collection were published by Brazilian publishers, from the cities of São Paulo and Rio de Janeiro, and from abroad, from France, Italy, Germany and Belgium, and were used in the cities of Jaraguá, Bomfim (Silvânia) and the City of Goiás. The published works mainly cover salon music, popular music and sacred music. There is repertoire for band, cinema orchestra, piano solo, voice and piano and vocal groups with or without instrumental accompaniment. This work intends to contribute to the study of musical activities in the period and to the organization, maintenance and dissemination of the Balthasar de Freitas’s collection, currently one of the main witnesses of the musical past of Goiás.